Pursuit of the Ph.D. - Kerlin, Scott P. (Education Policy Analysis Archives, 1995)
he thesis is put forward that changes in public policy which originally promoted broad access to higher education are leading to the diminished likelihood that minorities, those from low-income backgrounds and females in underrepresented disciplines will pursue, or be able to complete, the doctorate. By reviewing a wide range of research literature and statistical reports on the status of doctoral education in the U.S. & Canada, a detailed sociological portrait of those who pursue the Ph.D. is presented. Recommendations are given for further research on doctoral education, particularly in areas of attrition,retention, student indebtedness, social stratification, and post-doctoral career plans.